PERTIMBANGAN HAKIM DALAM MEMERIKSA DAN MEMUTUS PERKARA ITE BERMUATAN SARA (STUDI PUTUSAN NOMOR 169/PID.SUS/2017/PN.RAP) - Dini Adhilia; Vincentius Patria Setiawan (Sebelas Maret University, 2023)
The purpose of this research is to find out the consideration of judges in examining and deciding case of hate speech and hostility cases that contain ethnicity, religion, racial, and inter-group (SARA) to Decision Number: 169/Pid.Sus/2017/PN Rap. This research is a perspective normative legal research, and applied. The approach used is case approach based on case study. The type and sources in this research use primary and secondary legal materials with legal material collection techniques in form of literature studies. The analysis technique uses syllogistic deduction by formulating the facts from the mayor premise and minor premise. The results of the research and subsequent discussion shows in deciding and examining cases of hate speech, there must be at least two pieces of evidence and from the facts that appeared at trial, apart from that there were also aggravating and mitigating circumstances so that the judge's conviction emerged to sentence him to imprisonment 2 (two) years and a fine of Rp. 1,000,000,000.00 (one billion rupiah) with the provision that if the fine is not paid it will be replaced by imprisonment for 3 (three) months.